Resilience and Work Engagement of Nurses at Hasanuddin University Hospital: Post Covid-19 Services - Nurmala Sari; Hapsah Hapsah; Priska Anggelina Wong; Maisya Finistri Marzuki; Milka Murua; Mirnah Amir Makkau (Universitas Muhammadiyah Yogyakarta, 2022)
The Covid-19 pandemic has made all healthcare providers experience extraordinary turbulence and tested the resilience of health workers towards burnout syndrome, especially nurses as front liners who serve 24 hours. Anxiety conditions and excessive workloads impact decreasing nurse work engagement in hospitals. This study aims to determine resilience's effect on nurses' work engagement at Hasanuddin University Hospital. The method used in this study is a quantitative study using an analytical observational design with a cross-sectional study approach. This research was conducted at Unhas Hospital in August 2022. The total sample is 166 people who are nurses who have worked for 1 year at Unhas Hospital. Data were collected with an online questionnaire using google forms which was divided into 3 parts, namely respondent characteristics, statements related to nursing resilience (CD-RISC), and statements related to work engagement (EES). Data were analyzed using descriptive tests and the Pearson correlation test on SPSS 25. The results showed that resilience affected work engagement (p<0.05). Designing a regular resilience program in the human resources department is crucial to enhance nurses' resilience capacity and work engagement.